Hak Konstitusional Terkait Hak Ekonomi Pencipta dan Pelaku Pertunjukan Berdasarkan UU No. 28 Tahun 2014 tentang Hak Cipta - Gabriel Tololiu, Yudi; Tri Srilaksmi, Ni Ketut; Adi Susila, I Nyoman (Universitas Medan Area, 2025)
This study discusses how the constitutional rights related to the economic rights of creators and performers are regulated under the Copyright Law, and how the future regulations (ius constituendum) will be regulated regarding the economic rights of creators and performers. This study is a normative legal study using a statute approach and a case approach. Based on the results of the analysis, constitutional rights related to the moral rights and economic rights of creators have been regulated in Article 5 paragraph (1) and Article 9 paragraph (1) of the Copyright Law, while the economic rights of performers are regulated in Article 23 of the Copyright Law. However, in the case of performers using other people's creations commercially, there are differences in the regulations in the Copyright Law regarding the economic rights that must be paid to the creator. Article 9 paragraph (3) essentially states that anyone who wants to use a work of creation commercially must first obtain the creator's permission, but Article 25 paragraph (3) sets this aside because by paying compensation through LMK it is considered to have obtained permission from the copyright holder.